Prognostic influence of Barrett's oesophagus and Helicobacter pylori infection on healing of erosive gastro-oesophageal reflux disease (GORD) and symptom resolution in non-erosive GORD: report from the ProGORD study. Issue 6 (11th May 2005) - Malfertheiner, P; Lind, T; Willich, S; Vieth, M; Jaspersen, D; Labenz, J; Meyer-Sabellek, W; Junghard, O; Stolte, M
Abstract : Background: Adequacy of acid suppression is a critical factor influencing healing in gastro-oesophageal reflux disease (GORD). The European prospective study ProGORD was set up to determine the endoscopic and symptomatic progression of GORD over five years under routine care, after initial acid suppression with esomeprazole. We report on factors influencing endoscopic healing and symptom resolution during the acute treatment phase. Methods: Patients with symptoms suggestive of GORD underwent endoscopy and biopsies were obtained from the oesophagus for diagnosis of abnormalities, including Barrett's oesophagus (BO). Data from 6215 patients were included in the "intention to treat" analysis, 3245 diagnosed as having erosive reflux disease (ERD) and 2970 non-erosive reflux disease (NERD). ERD patients were treated with esomeprazole 40 mg for 4–8 weeks for endoscopic healing while NERD patients received 20 mg for 2–4 weeks for resolution of heartburn symptoms. Results: Endoscopic healing occurred overall in 87.7% of ERD patients although healing was significantly lower in those with more severe oesophagitis (76.9%) and in those with BO (72.4%), particularly in Helicobacter pylori negative BO patients (70.1%). Age, sex, and body mass index appeared to have no significant impact on healing. Complete heartburn resolution was reported by 70.4% of ERD patients and by 64.8% of NERD patients at the last visit. Only H pylori infection had a significant influence on complete heartburn resolution in the NERD group (68.1% and 63.7% for H pylori positive and H pylori negative, respectively; p = 0.03). Conclusion: The presence of Barrett's mucosa, as well as severe mucosal damage, exerts a negative impact on healing. H pylori infection had a positive influence on healing in ERD patients with coexistent BO but no influence on those without BO.